The Impact of Organized Crime on Societal Security: Algeria as Case of Study تأثير الجريمة المنظمة على الأمن المجتمعي: الجزائر حالة دراسة - سليماني سهام (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
ساهمت مدرسة كوبنهاغن لأبحاث السلام والأمن في توسيع مفهوم الأمن ليشمل الأمن المجتمعي والذي وصفه باري بوزان بأنه من أعقد الأمون، مقابل ظهور مصادر جديدة للتهديدات الأمنية ذات طبيعة لاتماثلية وغير متكافئة القوة على غرار الجريمة المنظمة والتي تجاوز تأثيرها الحدود الوطنية للدولة كما أضحت لها تداعيات على الأمن المجتمعي، وهو موضوع هذه الورقة البحثية والذي تتم معالجته بطرح الاشكالية التالية:ما هي تداعيات الجريمة المنظمة بمختلف أشكالها على الأمن المجتمعي في الجزائر؟ Abstract: The Copenhagen School for Peace and Security Research contributed to expanding the concept of security to include societal security, which Barry Buzan described as one of the most complex of security, In contrast to the emergence of new sources of security threats of an asymmetric nature and unequal power, such as organized crime, whose impact has gone beyond the which is the subject of this research paper, which is addressed by asking the following problem: What are the repercussions of organized crime in its various forms on societal security in Algeria?